Green criminology and the reconceptualization of school violence: comparing green school violence and traditional forms of school violence for school children - Barrett, Kimberly L. (Critical criminology, 2016)
School crime and violence continue to be important topics of criminological inquiry. Forms of violence that have received much attention from criminologists include school gun violence, assaults, and bullying. What appears missing from criminological studies are analyses of different forms of violent victimization imposed on school children related to environmental injustice, pollution, and exposure to toxins. In this article, we argue for the interpretation of these harms as violent victimizations. To facilitate this, we draw upon definitions of violent victimization developed in green criminology, conceptualizing exposure to environmental toxins as violent assault, and introduce the term green school violence (GSV). Next, we draw upon the medical, environmental, and public health literature to offer a series of examples of GSV in the United States, discuss numerous environmental hazards present in American schools, and describe their scope and severity. A conservative estimate of the frequency of GSV suggests that far more school children are victimized by GSV than forms of interpersonal acts of violence.